2018
DOI: 10.3389/fmicb.2017.02654
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Quorum Sensing Anti-Activators on Pseudomonas aeruginosa Virulence Traits and Transcriptome

Abstract: In the opportunistic pathogen Pseudomonas aeruginosa, quorum sensing (QS) via acyl-homoserine lactone (AHL) signals coordinates virulence gene expression. AHL signals must reach a critical threshold before enough is bound by cognate regulators LasR and RhlR to drive transcription of target genes. In addition, three anti-activator proteins, QteE, QscR, and QslA, sequester QS regulators to increase the threshold for induction and delay expression of QS target genes. It remains unclear how multiple anti-activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 63 publications
5
48
0
Order By: Relevance
“…The activated LuxR-type receptors then alter gene expression levels to initiate behaviors that will benefit the group and/or are only achievable as a bacterial community, including a range of virulence phenotypes such as biofilm formation, protease and toxin production, and motility mechanisms (Lyczak et al, 2000). The pathogen P. aeruginosa has a fairly complex QS circuit involving three LuxR-type receptors (LasR, RhlR, and QscR) (Asfahl and Schuster, 2018), two AHL signals ( N -(3-oxo)-dodecanoyl HL, OdDHL [compound 1 in Fig. 1A] and N -butyl HL, BHL) produced by LuxI-type synthases (LasI and RhlI, respectively), and the Pseudomonas quinolone signal (PQS), which binds to PqsR, a transcription factor unrelated to LuxR-type receptors (Welsh and Blackwell, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated LuxR-type receptors then alter gene expression levels to initiate behaviors that will benefit the group and/or are only achievable as a bacterial community, including a range of virulence phenotypes such as biofilm formation, protease and toxin production, and motility mechanisms (Lyczak et al, 2000). The pathogen P. aeruginosa has a fairly complex QS circuit involving three LuxR-type receptors (LasR, RhlR, and QscR) (Asfahl and Schuster, 2018), two AHL signals ( N -(3-oxo)-dodecanoyl HL, OdDHL [compound 1 in Fig. 1A] and N -butyl HL, BHL) produced by LuxI-type synthases (LasI and RhlI, respectively), and the Pseudomonas quinolone signal (PQS), which binds to PqsR, a transcription factor unrelated to LuxR-type receptors (Welsh and Blackwell, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
“…1A] and N -butyl HL, BHL) produced by LuxI-type synthases (LasI and RhlI, respectively), and the Pseudomonas quinolone signal (PQS), which binds to PqsR, a transcription factor unrelated to LuxR-type receptors (Welsh and Blackwell, 2016a, b). It has been proposed that targeting LasR may have the largest impact on QS-related virulence in P. aeruginosa (Galloway et al, 2012), since LasR activation directly upregulates certain virulence phenotypes (e.g., proteases, biofilm) and indirectly upregulates other virulence phenotypes (e.g., pyocyanin, rhamnolipid) through positive regulation of both the RhlR and PqsR systems (Asfahl and Schuster, 2018; Welsh and Blackwell, 2016a, b). Therefore, considerable efforts have been directed toward designing molecules to antagonize LasR and thereby block its associated virulence phenotypes, with notable contributions from the Bassler (O’Loughlin et al, 2013), Blackwell (Gerdt et al, 2014; Geske et al, 2007; Moore et al, 2015; O’Reilly and Blackwell, 2016), Greenberg (Muh et al, 2006; Müh et al, 2006), Meijler (Amara et al, 2011; Amara et al, 2009), Spring (Galloway et al, 2011; Hodgkinson et al, 2012), and Suga (Smith et al, 2003a; Smith et al, 2003b) laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of AHL production in the presence of DADS and MMFDS may be due to the suppression of luxR expression caused by luxI , either at the transcription or translation level. Previous study has been demonstrated that both AHL and LasR are essential for achieving maximal activation of the lasB gene (Asfahl & Schuster, ).…”
Section: Resultsmentioning
confidence: 99%
“…10, 2018 r Journal of Food Science 2555 translation level. Previous study has been demonstrated that both AHL and LasR are essential for achieving maximal activation of the lasB gene (Asfahl & Schuster, 2017).…”
Section: Effect Of Qsis On Ahl Production In H Alvei H4mentioning
confidence: 98%
“…That is, while cell density or even cell distance have provided the context for QS initiation, it is more likely the autoinducer concentration proximal to a QS-responding cell that is the predominant factor . Indeed, the contextualization of QS activity, particularly its contributions to multicellularity, has been the motivation of several hypotheses including diffusion (Redfield, 2002) or efficiency (Hense et al, 2007) sensing, as well as attributions relative to the 'social good' (Parsek and Greenberg, 2005;Sandoz et al, 2007;Dandekar et al, 2012;Asfahl and Schuster, 2018).…”
Section: Introductionmentioning
confidence: 99%